TRANSPLANTASI DALAM KAJIAN ISLAM - Niswatin Mubarriroh (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2021)
This article aims to provide a perspective on transplantation of Islamic religious law. By using analytical descriptive method. The author tries to explore how the opinions of scholars respond to organ transplants or body parts from humans and animals. Transplantation is one of the findings of modern medical technology with a working method in the form of moving tissues or organs from one place to another. This can be done on one individual or two individuals. Transplants are carried out with the aim of treating serious illnesses, if the transplant is not carried out it will result in death and treatment is carried out to avoid physical disabilities that will cause psychological disorders in the patient. In this case, when viewed from the point of view of the study of Islamic sharia law. Scholars divide it into two major parts of the discussion, namely. Implantation of tissues/organs taken from the same body and implants of tissues/organs taken from other individuals. Among the scholars who allow it is DR. Yusuf Qordhowi (Fatawa Mu'ashiroh II/530), Abdurrahman bin Sa'di (1307-1367H.), DR. Abd. Jalil Syalabi (Daily Syarq Ausath edition 3725, 8/2/1989M.). This study is important to know, because it is an effort to determine the law regarding the advancement of modern health as an effort to benefit the people.